(untitled) (World Bulletin of Management and Law, 2023)
This article describes the state of the penitentiary system in Uzbekistan in connection with the ongoing reforms in the system. In addition, suggestions and recommendations will be made based on foreign experience in improving the existing regulations to ensure the rights and freedoms of persons detained in penitentiaries. In addition, the author made recommendations on setting minimum standards for the employment of convicts in production enterprises owned by private businesses, the length of service of convicts, the elimination of problems related to the transfer of convicts from one institution to another